Emotion in Language: An Appraisal Analysis on Harry Maguire's Instagram Comments - Sudis, Zidan Amrullah As; Ishlahiyah, Mazroatul (Universitas PGRI Semarang, 2025)
Many people used Instagram massively as a convenient way to express their feelings and emotions through the comment sections. This phenomenon led to a variety of linguistic expressions of emotions, making it an interesting subject to study. After Harry Maguire scored an own goal while defending England against Scotland, he became a controversial figure. As a consequence, netizens were critical of him on his personal Instagram account. Using Martin and White's (2005) appraisal theory and Izard's (2009) emotion types, this study aimed to reveal how netizens' appraisal systems were expressed and how emotions were reflected in these appraisal types towards Harry Maguire. This research used a descriptive qualitative method with a discourse analysis approach. The data of this study consisted of some comments from actual accounts with high levels of insight and emotions that were relevant to the theory of appraisal and emotions. As a result, of the 35 comments, there are 42 appraisal types used by netizens. The details are that all appraisal types (attitude, engagement, and graduation) are used, except for the focus on graduation. Engagement was most dominantly used with a total of 12 monogloss subsystems. This represents netizens on the supportive side of Harry Maguire. In this case, netizens express emotions in language through the appraisal system, typically utilizing positive basic emotions. Netizens tend to express positive emotions and their appraisals based on the worth of a significant object that is important and able to represent the country, notwithstanding the controversy surrounding this situation.